Legacy of Dr. Saul Hertz - Marina S. Sheremeta; Maria O. Korchagina; Alexey A. Trukhin; Galina A. Mel'nichenko (Терапевтический архив)
Saul Hertz was a physician and scientist who invented and implemented the use of radioactive iodine (RAI) for medical purposes. The history of the development of this new non-invasive and effective method of treatment began in 1936, when Saul Hertz asked Karl Compton, president of the Massachusetts Institute of Technology: "Is it possible to artificially make iodine radioactive?" at the scientific session. The positive response was the beginning of Saul Hertz’s research in the field of nuclear medicine. Together with physicist Arthur Roberts, he studied the pharmacokinetics of radioactive isotopes of iodine and the possibility of using them for the diagnosis and treatment of thyroid disease (TD). In 1938, with the release of 131I, which emits gamma and beta rays and has a half-life of 8 days, RAI could be used not only in experiments, but also in clinical practice. On March 31, 1941, Dr. Saul Hertz performed the first RAI therapy for thyrotoxicosis. Nowadays, March 31 is called World Theranostics Day. Subsequently, Saul Hertz became the founder of the radionuclide treatment of TD, and based on the results of his work, the principles of RAI therapy for differentiated TD were developed. Currently, there are Dr. Saul Hertz Archives in Greenwich (Connecticut, USA) that store the works of this great physician and scientist.